Mechanism and Potential Target of Blood-Activating Chinese Botanical Drugs Combined With Anti-Platelet Drugs: Prevention and Treatment of Atherosclerotic Cardiovascular Diseases - Li, Dan; Li, Yujuan; Yang, Shengjie; Yu, Zongliang; Xing, Yanwei; Wu, Min (Frontiers in Pharmacology, 2022)
Atherosclerotic cardiovascular diseases (ASCVDs) are the most important diseases that endanger people’s health, leading to high morbidity and mortality worldwide. In addition, various thrombotic events secondary to cardiovascular and cerebrovascular diseases need must be considered seriously. Therefore, the development of novel anti-platelet drugs with high efficiency, and fewer adverse effects has become a research focus for preventing of cardiovascular diseases (CVDs). Blood-activation and stasis-removal from circulation have been widely considered as principles for treating syndromes related to CVDs. Blood-activating Chinese (BAC botanical drugs, as members of traditional Chinese medicine (TCM), have shown to improve hemodynamics and hemorheology, and inhibit thrombosis and atherosclerosis. Modern medical research has identified that a combination of BAC botanical drugs and anti-platelet drugs, such as aspirin or clopidogrel, not only enhances the anti-platelet effects, but also reduces the risk of bleeding and protects the vascular endothelium. The anti-platelet mechanism of Blood-activating Chinese (BAC) botanical drugs and their compounds is not clear; therefore, their potential targets need to be explored. With the continuous development of bioinformatics and “omics” technology, some unconventional applications of BAC botanical drugs have been discovered. In this review, we will focus on the related targets and signaling pathways of anti-atherosclerotic treatments involving a combination of BAC botanical drugs and anti-platelet drugs reported in recent years.